What is the trade response of the regional grouping in the GCC Countries? - Al-Mawali, N.; Salim, Ruhul (Thammasat University, 2011)
This paper examines whether the GCC exerted any trade enhancing impact on its members by employing standard augmented gravity model as well as stochastic frontier gravity model. Panel data sets are constructed over the period of 1980 to 2008 for imports and exports of the bloc's main trading partners along with GCC countries. Several diagnostic tests were run to check and rectify possible problems of heteroskedasticity and autocorrelation as well as cross-sectional dependence. The empirical result shows that most of the variables have desired signs and turn out to be statistically significant. Importantly, the major finding is that the trade enhancing effect of the bloc is significant.